Given:
The acceleration of the particle is,
![a=-4x](https://img.qammunity.org/2023/formulas/physics/college/zb6ix1qh457s9do3ddgtor59wfsupfth2e.png)
The particle was in origin with velocity,
![v_o=+4\text{ m/s}](https://img.qammunity.org/2023/formulas/physics/college/6r0jf76sj9s4jsr3pjer5qtalxfq5ujwsh.png)
To find:
a) Find velocity as a function of x
b) Maximum position of the particle
c) Position as a function of time.
Step-by-step explanation:
(a)
The acceleration is,
![\begin{gathered} a=(dv)/(dt) \\ =(dv)/(dx)*(dx)/(dt) \\ =v(dv)/(dx) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/bug76dlqskenl81i5443sqgrbnjqu3iisl.png)
According to the question,
![\begin{gathered} v(dv)/(dx)=-4x \\ vdv=-4xdx \\ \int vdv=\int-4xdx \\ (v^2)/(2)=-(4x^2)/(2)+c \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/to494r5vpiu7uqi0di6wzp1wpt4tefroul.png)
Here, 'c' is the integration constant.
Now, applying the condition at the origin, we can write,
![\begin{gathered} ((4)^2)/(2)=-(4*0)/(2)+c \\ (16)/(2)=c \\ c=8 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/5ty5qysa8sa1l3n2gzuj7z5u3f2ss84esh.png)
Now, the velocity is,
![\begin{gathered} (v^2)/(2)=-(4x^2)/(2)+8 \\ v^2=-4x^2+16 \\ v=√(16-4x^2) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/5zhfr54f34yh17g6rcd94tatn1vmk9koox.png)
Hence, the velocity as a function of x is,
![v=√(16-4x^2)](https://img.qammunity.org/2023/formulas/physics/college/6qn9kxelkut86kmq5orqwc3fhmjxcvpzj2.png)
(b)
At the maximum position, the speed of the particle becomes zero.
So, the maximum position is,
![\begin{gathered} 0=√(16-4x^2) \\ 16-4x^2=0 \\ 4x^2=16 \\ x^2=(16)/(4) \\ x^2=4 \\ x=\pm2 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/82hq51tprxnfaky53tvwl9j4lu4jfgbb52.png)
Hence, the position of the particle is,
![x=\pm2\text{ m}](https://img.qammunity.org/2023/formulas/physics/college/apnsoxuvd1r707tfrx9kebp535467atw00.png)
(c)
Now, the velocity of the particle is,
![\begin{gathered} v=(dx)/(dt)=√(16-4x^2) \\ dx=√(16-4x^2)dt \\ (dx)/(√(16-4x^2))=dt \\ \int(dx)/(√(16-4x^2))=\int dt \\ (1)/(2)sin^(-1)((x)/(2))+k=t \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/w7fjg6vi50h7n2xbgcwq5fo637rekg0ejd.png)
Here, 'k' is the integration constant.
Hence, the position as a function of time is,
![(1)/(2)sin^(-1)((x)/(2))+k=t](https://img.qammunity.org/2023/formulas/physics/college/uz9lw8hxy01abjeia5g4k5t5lwhmximgat.png)